Congress of Neurological Surgeons Systematic Review and Evidence-Based Guideline on the Incidence of Tethered Cord Syndrome in Infants With Myelomeningocele With Prenatal Versus Postnatal Repair. Issue 3 (16th August 2019) - Mazzola, Catherine A; Tyagi, Rachana; Assassi, Nadege; Bauer, David F; Beier, Alexandra D; Blount, Jeffrey P; Durham, Susan R; Flannery, Ann Marie; Klimo Jr, Paul; McClung-Smith, Catherine; Nikas, Dimitrios C; Rehring, Patricia; et al.
Abstract: BACKGROUND: The incidence of spina bifida (SB) is higher in the developing world as compared to the United States because of folic acid deficiency during pregnancy. Advances in technology have made prenatal repair of myelomeningocele (MM) possible. OBJECTIVE: The objective of this guideline was to determine if there is a difference in the rate of development of tethered cord syndrome (TCS) in infants who had prenatal closure compared to infants who had MM repair after birth. METHODS: The Guidelines Task Force developed search terms and strategies to search PubMed and Embase for the relevant literature published between 1966 and September 2016. Strict inclusion/exclusion criteria were used. Full text articles were reviewed and, when appropriate, included as evidence. RESULTS: A total of 261 abstracts were reviewed. Fifty-four full-text articles were selected for further analysis. Three studies met inclusion criteria. CONCLUSION: There was Class II evidence from 1 study and Class III evidence from another 2 studies demonstrating that TCS develops in infants with prenatal MM closure at an equal or higher rate than with postnatal closure. There was an increased risk of development of inclusion cysts in infants who underwent in utero closure. Continued surveillance for TCS and/or the development of inclusion cysts in children with prenatal and postnatal closure of MM is indicated (Level II). Differences between prenatal and postnatal repair with respect to the development of TCS and/or inclusion cysts should be considered alongside other relevant maternal and fetal outcomes when deciding upon a preferred method for MM closure. The full guideline can be found at https://www.cns.org/guidelines/guidelines-spina-bifida-chapter-6 .